OC-089 Epigenetic Control of GI Inflammation Via the Methyl-Binding Protein MBD2. (4th June 2013) - Jones, G-R; Cook, P; Webb, L; MacDonald, A
Abstract : Introduction: Methyl-CpG binding protein domain protein-2 (Mbd2) is a transcriptional co-repressor that binds to methylated DNA. Mbd2 can recruit a nucleosome remodelling complex which contains chromatin remodelling and histone deacetylase properties. Mbd2 deficient mice are viable and fertile. However, they display a dysregulated immune phenotype with an aberrant T cell cytokine response and susceptibility to intestinal helminth infection (1). This immunological phenotype has not been explored in the GI tract. Aim: To assess the impact of Mbd2 deficiency on the activation status and cytokine production of naïve Mbd2-/- leucocytes isolated from murine small intestine (SI) and large intestine (LI) lamina propria (LP). Methods: All mice were bred in specific-pathogen free facilities at the University of Edinburgh. Mbd2-/- mice were produced as described previously (1). Single cell suspension of SI and LI LP were isolated as previously described, n = 4 in each group, minimum 2 experiments (2). Controls were wildtype (WT) age and sex matched littermates. Cells were first stained with LiveDead blue (Life Technologies), FcR-Block and subsequently; CD11c, Ly6C, CD80, B220, CD11b, MHC(II), Ly6G, CD103, F4/80, CD40 and CD45. 4hr incubation with PMA/ionomycin/GolgiStop (BD bioscience) was performed for intracellular cytokine analysis with IFNgamma, IL-4, IL-13, IL-17 and TNFalpha. Samples were acquired using an LSRII and analysed with FlowJo (TreeStar), student t test was used with Prism (GraphPad) in statistical analyses. Results: Mbd2-/- mice showed significantly greater IFNgamma, TNFalpha and IL-17 but not IL-13 or IL-4 production in CD4+ and CD8+ lymphocytes isolated from SI and LI LP compared to WT controls. In addition surface activation markers CD80 and CD86 were significantly greater in Mbd2-/- CD103+CD11b+CD11c+ Dendritic cells and CD11b+CD11c+F4/80 macrophages from SI LP. Conclusion: These results show for the first time that epigenetic processes can regulate both antigen presenting cell activation status and T cell production of potentially damaging inflammatory cytokines at the mucosal-environmental barrier. They also identify methyl-binding proteins and/or genes that they regulate as exciting new targets for therapeutic modulation of GI inflammation. Disclosure of Interest: None Declared References: Hutchins ASA et al. Cutting edge: a critical role for gene silencing in preventing excessive type 1 immunity. J Immunol.2005 175(9):5606–5610. Little MC et al. The characterization of intraepithelial lymphocytes, lamina propria leukocytes, and isolated lymphoid follicles in the large intestine of mice infected with the intestinal nematode parasite Trichuris muris. J Immunol. Am Assoc Immnol; 2005; 175(10):6713–6722.